Police contact with individuals with intellectual or developmental disabilities: a special issue introduction. Issue 3 (1st April 2022) - Wallace, Danielle; McGhee Hassrick, Elizabeth
Abstract : Purpose: In this paper, the authors summarize the empirical and theoretical gaps in understanding of police contact with individuals with intellectual and/or developmental disabilities at the individual, interactional, organizational and systems level and introduce the special issue papers which address these gaps. The authors close with a discussion of future directions for research in this area. Design/methodology/approach: The authors' objective in producing this issue was to create a platform to generate and facilitate research in this area. The authors chose papers that represented research that could "move the needle" around the understanding of policing and intellectual and/or developmental disabilities. Findings: The papers in this special issue reflect four thematic areas: (1) the nature of interactions between the police and individuals with intellectual and/or developmental disabilities; (2) police interactions about individuals with intellectual and/or developmental disabilities with criminal justice systems, social services and mental health services, (3) experiences of the police when encountering individuals with intellectual and/or developmental disabilities and finally, (4) the experiences within police encounters of individuals with intellectual and/or developmental disabilities. Originality/value: Research on intellectual and/or developmental disabilities is still in its infancy, particularly within the field of criminology and criminal justice. This special issue brings together innovative international research that adds critical information surrounding the nature of interactions between the police and individuals with intellectual and/or developmental disabilities, the experience for both parties during that interaction and the context of these interactions in the larger organizational ecosystem of criminal justice organizations and social service agencies.